COWAN, Jane K. (organizadora) 2000. Macedonia: The Politics of Identity and Difference - Boskovic, Aleksandar (Campos - Revista de Antropologia, 2003)
Review of Macedonia: The Politics of Identity and Difference, edited by Jane Cowan, published in 2000.